ROLE PERFORMANCE AND CHALLENGES OF MALE SINGLE-PARENT FAMILIES IN THE CENTRAL REGION OF GHANA - Amissah, Augustina Araba; Mensah, John Victor; Antwi, Kwabena Barima (Advances in Social Sciences Research Journal, 2015)
This study investigated the role performance and challenges of male single-parents in the Central Region of Ghana using a descriptive and evaluative survey approach. A multi-stage sampling procedure was adopted to select 300 male single-parents for the study. Pretested questionnaire and interview schedule were used to collect the data. The Statistical Product and Service Solutions (SPSS) (Version 16.0) software was used to analyse the data. The major findings of the study were that the performance of instrumental and expressive roles had affected aspects of lives of the respondents. The major challenges faced by the respondents included time constraints, fatigue and loneliness. It is recommended that the local government, central government and non-governmental organizations should undertake human resource development programmes in the Central Region to equip male single-parents with the necessary knowledge, skills and attitudes for the performance of both expressive and instrumental roles in the home. Family life professionals should also expand their programmes to cater for the interests and struggles of male single-parents.